2´OMethylRNA EFG1 antisense oligomer to control Candida albicans filamentation - Araújo, Daniela (2019)
Antisense oligomers (ASO) and their analogues have been successfully utilized to silence gene expression for the treatment of many human diseases, however the control of yeast´s virulence determinants have never been exploited before. In this sense, this work is based on the key hypothesis that if a pathogens genetic sequence is a determinant of virulence, it will be possible to synthesize a nucleic acid mimic based on antisense therapy (AST) that will bind to the mRNA produced, blocking its translation into protein and consequently reducing the pathogen virulent phenotype. EFG1 is an important determinant of virulence that is involved in regulation of Candida albicans switch from yeast to filamentous form. Thus, our main goal was to design and synthesize an ASO targeting the EFG1 mRNA and to validate its in vitro applicability in order to control C. albicans filamentation. For that, an ASO against EFG1 was designed, including 2OMethylRNA chemical modification, through bioinformatic tools. The fluorescence in situ hybridization (FISH) was performed and demonstrated that the ASO was able to penetrate Candida cell wall with high sensitivity and specificity. To determine the effect of anti-EFG1 2OMe, the gene level expression, protein translation inhibition and reduction of filamentation reduction were analysed. The results show that the anti-EFG1 2OMe oligomer was able to significantly reduce the levels of EFG1 gene expression (around 58%) and of Efg1p protein translation (approximately 56%), as well as effectively prevent filamentation of C. albicans cells (by 80%). Moreover, it was verified that anti-EFG1 2OMe keep the efficacy in different simulated human body fluids. Undeniably, this work provides potentially valuable information for future research into the management of Candida infections, regarding the development of a credible and alternative method to control C. albicans infections, based on AST methodology.